Densification and grain growth behavior of highly dense MgO ceramics in pressureless sintering. Issue 8 (September 2015) - Li, Shengli; Song, Chunjun; Qin, Xiaoying; Zeng, Zhi
Abstract: Highly dense MgO ceramics were fabricated by two step pressureless sintering without sintering additives, and their sintering kinetics and grain growth behavior were studied. The results indicate that a "kinetic window" in which the grain growth is suppressed exists. An activation energy Q =196.39±5.76 kJmol −1 for grain growth is estimated. In the two step sintering with optimized parameters, high dense (relative density 98.0%) samples with both a mean grain size of 21±2 um and mean hardness H v =6.1±0.2 GPa are obtained.